Maqasid Al-Syari‘ah Dalam Pensyariatan Puasa Ramadhan: “Analisis Makna Yang Terkandung Dalam QS. AlBaqarah Ayat 183–187” - muhammad fahri (FIRDAUS, 2025)
Studies on Ramadan fasting generally focus on jurisprudential aspects, character education, and spirituality, while research integrating the tahlili interpretation method with the maqāṣid al-syari‘ah approach toward the entirety of Qur'an Surah Al-Baqarah verses 183–187 remains limited. In fact, these verses not only contain legal regulations regarding fasting but also explain the objectives, wisdom, and benefits intended by its legislation. Therefore, this study aims to analyze the content of Surah Al-Baqarah verses 183–187 through the tahlili interpretation method and to identify the maqaṣid al-syari‘ah embedded within them. This research employs a qualitative library research approach. Primary data were obtained from the Qur'an and major classical and contemporary exegeses, including Jami‘ al-Bayan by al-Ṭabari, Tafsir al-Qur’anal-‘Aẓim by Ibn Kathir, Al-Jami‘ li Aḥkam al-Qur’anby alQurṭubi, Al-Tafsir al-Munir by Wahbah al-Zuḥaili, and Tafsir al-Miṣbaḥ by M. Quraish Shihab. Secondary data were collected from scholarly journal articles discussing fasting and maqaṣid al-syari‘ah. Previous studies by Fauzi focused on character education, Hidayat examined the social implementation of maqaṣid al-syari‘ah, and Khasanah explored the spiritual dimensions of fasting. Unlike these studies, the present research specifically analyzes the fasting verses using the tahlili interpretation method with maqaṣid al-syari‘ah as the primary analytical framework. The findings reveal that the legislation of Ramadan fasting embodies the fundamental objectives of Islamic law, namely the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal). Therefore, Ramadan fasting should be understood not merely as a ritual obligation but also as a comprehensive instrument for achieving individual and social welfare in accordance with the universal objectives of Islamic law.